Flexural behavior of precast concrete slab with steel fibre concrete topping - Mansour, Farnoud Rahimi (2010)
Considerable interest has been developed in using fibres is concrete to increase the load-carrying capacity of structures in service. Fibre reduces brittleness of concrete and improves its engineering properties such as tensile, flexural, impact, fatigue, load bearing capacity after cracking and toughness. Among fibres, steel fibre is one of the most popular and widely used fibres in both research and practice. Steel fibre-reinforced concrete (SFRC) has been used increasingly in recent years and has applied to various structural components. It is also known that using 0.5 – 2.5 % fibre in concrete mix can significantly improve the concrete properties. In recent years, it has been used as a strengthening technique for concrete slabs. Cement-base bonded overlay technique consists of applying a thin layer of SFRC onto the existing slab. Beneficial effect of fibre reinforcement on the durability of cement-base bonded overlay has been amply demonstrated by previous researchers. The objective of this research is investigation on flexural behavior of precast concrete slab with steel fibre concrete topping. The parameter investigated includes steel fibre volume fraction and surface condition between old and new concrete. A series of 108 specimens (cube, cylinder and prism), without and with three different steel fibre volumes were investigated by ratio of 0.7%, 1.0% and 1.5% to determine the optimum percentage volume of steel fibre in application to reinforced concrete topping. To reinforce the concrete overlay, hooked-end steel fibres was used; length of 30 mm and diameter of 0.75 mm. These slabs have three different surface textures between the substrate and concrete topping which include smooth as-cast and roughened in both longitudinal and transverse direction. The results show good reliability on using SRFC as concrete topping replacing the conventional construction method. The highest bond strength was achieved with roughening the top substrate in transverse direction which can sustain 2.5 times more moment compared with the calculated values.